2005
DOI: 10.1021/jf048867u
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aminophospholipids in the External Layer of Liposomes Protect Their Component Polyunsaturated Fatty Acids from 2,2‘-Azobis(2-amidinopropane)- dihydrochloride-Mediated Lipid Peroxidation

Abstract: We showed in our previous study that docosahexaenoic acid-rich phosphatidylethanolamine in the external layer of small-size liposomes, as a model for biomembranes, protected its docosahexaenoic acid from 2,2'-azobis(2-amidinopropane)dihydrochloride- (AAPH-) mediated lipid peroxidation in vitro. Besides phosphatidylethanolamine, both phosphatidylserine and an alkenyl-acyl analogue of phosphatidylethanolamine, phosphatidylethanolamine plasmalogen, are reported to possess characteristic antioxidant activities. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For instance, phospholipids containing two DHA groups were peroxidized at the similar rates or sometimes a lower rate than phospholipids containing a DHA and a palmitic acyl group when put into liposomes composed of phospholipids with saturated fatty acyl groups, contrary to what would be predicted based on the peroxidizability indexes (Norris et al, 2012). Additionally, phosphatidylethanolamine with DHA appears to have protective effects against peroxidative damage when it is positioned in the outer leaflet of liposomes (Kubo et al, 2005). If the peroxidation index is potentially neither a good estimate of the actual peroxidizability of free fatty acids, nor of the peroxidizability of fatty acyl groups on phospholipids, it is unclear why it is often correlated with maximum lifespan, as well as actual measures of oxidative damage (Aguilar-Toral et al, 2014;Hulbert et al, 2014;Jeon et al, 2001;Naudí et al, 2013;Pamplona et al, 2004Pamplona et al, , 2000Pamplona et al, , 1999aPamplona et al, , 1998Pamplona et al, , 1996.…”
Section: Potentially Inaccurate Estimates: Maximum Lifespan and Peroxmentioning
confidence: 79%
See 2 more Smart Citations
“…For instance, phospholipids containing two DHA groups were peroxidized at the similar rates or sometimes a lower rate than phospholipids containing a DHA and a palmitic acyl group when put into liposomes composed of phospholipids with saturated fatty acyl groups, contrary to what would be predicted based on the peroxidizability indexes (Norris et al, 2012). Additionally, phosphatidylethanolamine with DHA appears to have protective effects against peroxidative damage when it is positioned in the outer leaflet of liposomes (Kubo et al, 2005). If the peroxidation index is potentially neither a good estimate of the actual peroxidizability of free fatty acids, nor of the peroxidizability of fatty acyl groups on phospholipids, it is unclear why it is often correlated with maximum lifespan, as well as actual measures of oxidative damage (Aguilar-Toral et al, 2014;Hulbert et al, 2014;Jeon et al, 2001;Naudí et al, 2013;Pamplona et al, 2004Pamplona et al, , 2000Pamplona et al, , 1999aPamplona et al, , 1998Pamplona et al, , 1996.…”
Section: Potentially Inaccurate Estimates: Maximum Lifespan and Peroxmentioning
confidence: 79%
“…Moreover, the relative peroxidizabilities of free fatty acids may not always be relevant to how they act as acyl groups when attached to larger molecules (Cosgrove et al, 1987;Kubo et al, 2005;Norris et al, 2012;Wijesundera et al, 2008;Zerouga et al, 1995). For instance, phospholipids containing two DHA groups were peroxidized at the similar rates or sometimes a lower rate than phospholipids containing a DHA and a palmitic acyl group when put into liposomes composed of phospholipids with saturated fatty acyl groups, contrary to what would be predicted based on the peroxidizability indexes (Norris et al, 2012).…”
Section: Potentially Inaccurate Estimates: Maximum Lifespan and Peroxmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, the increased surface area of two 22:6 PUFA in PtdCho 22:6/22:6, even with its larger headgroup, might also favor its partitioning into the inner leaflet. It is well known that the charge on polar head groups, volume of the phosphoplipid, curvature of liposomes and molar ratios of phospholipids are all factors that can influence phospholipid distribution in liposomes [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that the synthesis of PE by this reaction may be directed towards repairing any damage to unsaturated fatty acid chains of phospholipids caused by reactive oxygen species under oxidative stress (Jasinka et al, 1996). In addition, as has already been observed in synthetic membranes, the arrangement of phospholipid molecules in the bilayer is a significant factor in determining resistance to freeradical attack during lipid peroxidation, and importantly in this respect, the primary amine group of PE and PS in the external layer possesses antioxidant activity, thus protecting the polyunsaturated fatty acids from lipid peroxidation (Kubo et al, 2005).…”
Section: Introductionmentioning
confidence: 97%